Ankylosing spondylitis and risk of venous thromboembolism: A systematic review and meta-analysis - Patompong Ungprasert (2018)
© 2016 Indian Chest Society | Published by Wolters Kluwer - Medknow Background: Several immune-mediated inflammatory disorders, such as rheumatoid arthritis, psoriatic arthritis, and systemic lupus erythematosus have been linked to an increased risk of venous thromboembolism (VTE). However, the data on ankylosing spondylitis (AS) are limited. Methods: We conducted a systematic review and meta-analysis of observational studies that reported odds ratio, relative risk, hazard ratio, or standardized incidence ratio comparing the risk of VTE and possible pulmonary embolism (PE) in patients with AS versus non-AS participants. Pooled risk ratio and 95% confidence intervals were calculated using a random-effect, generic inverse variance method of DerSimonian and Laird. Results: Of 423 potentially relevant articles, three studies met our inclusion criteria and thus, were included in the data analysis. The pooled risk ratio of VTE in patients with AS was 1.60 (95% confidence interval: 1.05-2.44). The statistical heterogeneity of this study was high with an I2of 93%. Conclusion: Our study demonstrated a statistically significant increased VTE risk among patients with AS.